Differential Predictors and Clinical Implications Associated With Long-Term Survivors in IDH Wildtype and Mutant Glioblastoma - Jiang, Haihui; Yu, Kefu; Cui, Yong; Ren, Xiaohui; Li, Mingxiao; Zhang, Guobin; Yang, Chuanwei; Zhao, Xuzhe; Zhu, Qinghui; Lin, Song (Frontiers in Oncology, 2021)
Background: Glioblastoma (GBM) is the most aggressive intracranial tumor which can be divided into two subtypes based on status of isocitrate dehydrogenase (IDH). A small fraction of patients after receiving standard treatment can be long-term survivors (LTS). This study was designed to disclose the predictors and clinical implications associated with LTS in IDH wildtype and mutant GBM. Methods: Patients who survived beyond five years after diagnosis of GBM were defined as LTS, while those with a survival less than one year were defined as short-term survivors (STS). A total of 211 patients with diagnosis of GBM in Beijing Tiantan Hospital from January 2007 to January 2015 were enrolled, including 44 (20.9%) LTS and 167 (79.1%) STS. The clinical, radiological and molecular features between groups were systematically compared. Results: Compared with STS, LTS were a subgroup of patients with a younger age at diagnosis (P=0.006), a higher KPS score (P=0.011), higher rates of cystic change (P=0.037), O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation (P=0.007), and IDH mutation (P=0.049), and more likely to have undergone gross total resection (P<0.001). Survival analysis demonstrated that LTS with wildtype IDH conferred a longer progression-free survival (66.0 vs. 27.0 months, P=0.04), but a shorter post-progression survival (46.5 months vs. not reached, P=0.0001) than those of LTS with mutant IDH. LTS with mutant IDH showed a trend towards increased survival after receiving re-operation (P=0.155) and reirradiation (P=0.127), while this clinical benefit disappeared in the subset of LTS with wildtype IDH (P>0.05). Conclusion: The prognostic value and therapeutic implications associated with LTS in GBM population significantly differed on the basis of IDH status. Our findings provide a new approach for physicians to better understand the two subtypes of GBM, which may assist in making more tailored treatment decisions for patients.